THE DEVELOPMENT STRATEGIES OF CASHEW INDUSTRY IN KENDARI CITY, SOUTHEAST SULAWESI - Asriani Asriani (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
The economic development of a region should refer to the agroindustry approach. An industry is not well developed due to the constraints of internal and external factors. This research aimed to identify the internal and external factors which could affect the development of cashew industry and determine the most effective alternative strategies applied in developing the cashew industry in Kendari Southeast Sulawesi Province. The data analysis technique used  Strength, Weakness, Opportuny and Threat (SWOT) methods. The results showed that the internal factors that most influenced the development of the cashew industry were availability of adequate labor and limited capital investment funds while the external factors that influence the development included the government support and limited access to markets. The alternative strategies of the cashew industry development in Kendari Southeast Sulawesi Province  include improving the marketing, maintaining the product quality and increasing the working capital.Keyword: development, strategy, cashew industry, SWOTAbstrakPembangunan ekonomi suatu daerah seharusnya mengacu pada pendekatan industri pertanian (agroindustri).  Suatu industri tidak berkembang dengan baik disebabkan oleh adanya hambatan faktor dari dalam maupun faktor dari luar.  Penelitian ini bertujuan untuk mengidentifikasi faktor internal dan eksternal yang dapat mempengaruhi pengembangan indutri mete serta menentukan alternatif strategi yang paling efektif diterapkan dalam mengembangkan industri  mete di Kota Kendari Provinsi Sulawesi Tenggara. Teknik analisis data yang digunakan adalah metode analisis Strengtsh, Weaknesses, Opportunies and Threats (SWOT). Hasil penelitian menunjukan bahwa faktor internal yang paling mempengaruhi pengembangan industri mete adalah tersedianya tenaga kerja yang memadai dan dana investasi modal yang terbatas, sedangkan faktor eksternal yang mempengaruhi adalah dukungan pemerintah dan terbatasnya akses pasar. Adapun alternatif strategi pengembangan industri mete di Kota Kendari Provinsi Sulawesi Tenggara adalah meningkatkan pemasaran, menjaga kualitas produk dan menambah modal kerja.Kata kunci: strategi pengembangan,industri mete, SWOT